Identification of Potential Hazards in Metal Fabrication Works Using Hazard Identification, Risk Assessment and Risk Control (HIRARC) in the Manufacturing Industry - Puvaneethan Visvanathan; Syahrun Neizam Mohd Dzulkifli; Zairudin Zaini (Progress in Engineering Application and Technology, 2026)
Metal fabrication works in the manufacturing industry are widely recognized as high-risk operations due to the involvement of hot work processes, heavy machinery, sharp materials, and manual handling activities. These conditions expose workers to various occupational safety and health hazards if not properly managed. This study aims to identify potential hazards, assess associated risks, and propose appropriate control measures for metal fabrication activities using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method. The study was conducted at the Universal Division, Factory 2 of PCA Group Sdn. Bhd., focusing on five major fabrication activities which is manual welding, robotic welding, grinding, buffing, and the use of hand tools. A qualitative case study approach was employed through direct site observations, photographic documentation, and review of existing safety records. Identified hazards were evaluated using a qualitative risk matrix based on likelihood and severity, followed by the recommendation of control measures according to the hierarchy of controls. The findings indicate that several fabrication activities present medium to high risk levels, particularly due to exposure to sparks, flying particles, electrical hazards, poor ergonomic postures, and inadequate personal protective equipment (PPE) compliance. The outcomes of this study provide a structured basis for prioritizing risk control measures and enhancing workplace safety practices in metal fabrication operations within the manufacturing industry.